Avaliação temporal dos casos de doenças tropicais negligenciadas no Estado do Paraná entre 2010-2019 - Santos, Keitia Couto dos (2021)
Neglected tropical diseases (NTDs) are caused by infectious agents or parasites, which are characteristic in low-income populations, with insufficient investment in research and development in order to advance control, prevention, and drug treatment. NTDs are endemic in 149 countries and affect more than one billion people worldwide. In this sense, the present study aims to carry out a temporal evaluation of the most frequent NTDs in the state of Paraná. The research was conducted based on data from the Information System for Notifiable Diseases (SINAN), in which the study of the sociodemographic profile was carried out through the variables: age group, sex, race, level of education, analysis of laboratory profile, and frequency of cases of Chagas disease, schistosomiasis, American tegumentary leishmaniasis (ATL), visceral leishmaniasis (VL) and dengue, in the population in the State of Paraná, between 2010 and 2019. From the results obtained, it was observed that the total number of cases of the diseases analyzed was 551 for Chagas disease, 463 for schistosomiasis; 3,389 for ATL; 268 for VL, and 714,080 for dengue. All diseases were more frequent in people aged between 20 and 59 years (59.71%; 68.68%; 66.69%; 57.46% and 60.44%, respectively). Regarding gender, it was observed that the diseases affected more males (50.45%, 68.25%, 74.42%, and 62.69%, respectively), being that only dengue was more frequent in females (53.18%). Concerning race, for all pathologies, the highest incidence was for white women (77.61%, 74.49%, 70.59%, 76.70%, and 66.42%, respectively). Lastly, regarding the level of education, for Chagas disease, ATL, and VL, the highest incidence occurred in people with incomplete elementary education (24.62%, 19.81%, and 9.20%, respectively), and for dengue and schistosomiasis, the highest frequency occurred in people with complete secondary education (18.94% and 16.86%, respectively). The study allowed us to obtain relevant information regarding the cases of the diseases analyzed in Paraná, showing that all of them are endemic in the state. Thus, we observe the importance of analyzing epidemiological data since it enables us to verify that despite government initiatives aimed at preventing such diseases, the frequency tends to be high for some of them. Hence, the constant mobilization of resources is necessary in order to enact the actions and control plans proposed by the Ministry of Health.